STILISTIKA MORFOLOGI AL-QURAN JUZ 30 - Hakim, M. Aunul (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2010)
There are some aspects of al-Quran miracle, among other are the language and content. Al-Quran is popularly known of using the popular vocabularies that are commonly used by the people but full up with meaning and decorated with beautiful language style. One of the characteristics is, in Juz 30 contains short verses, so that they can be read in a beautiful unity of style, and as consequence, it can be seen and felt harmonious in its rhythm and rhymes. Stylistics is a branch of language science that observes the language used in literary text, an interdisciplinary of linguistics and literature. There are found out the morphological stylistics in the Juz 30 in the form of one addition of morpheme in ‘wazan’, elimination of one morpheme in wazan, morpheme change in wazan, and change in word meaning. The morphemic addition in wazan is for example, addition of harf illat, tasydid, and ha’ saktah, while the elimination one morpheme such as the elimination of harf illat, harf ta’ mudlara’ah, ya’ mutakallim, and alif isim fail. The change of wazan can be found in the wazan jamak, masdar, isim shifat, fiil and isim. The change of meaning covers the widening meaning of isim, fi’il and word.